2016
DOI: 10.1063/1.4939629
|View full text |Cite
|
Sign up to set email alerts
|

An electrically resistive sheet of glial cells for amplifying signals of neuronal extracellular recordings

Abstract: Electrical signals of neuronal cells can be recorded non-invasively and with a high degree of temporal resolution using multielectrode arrays (MEAs). However, signals that are recorded with these devices are small, usually 0.01%-0.1% of intracellular recordings. Here, we show that the amplitude of neuronal signals recorded with MEA devices can be amplified by covering neuronal networks with an electrically resistive sheet. The resistive sheet used in this study is a monolayer of glial cells, supportive cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…A confluent glial bed could create a permissive environment for growth of axons closer to MEA electrodes than they might otherwise grow. Alternatively, glia could be an electrically resistive sheet that increases eAP amplitude across all electrodes by effectively decreasing the size of the electric field (Matsumura et al 2016). In neuronal cultures not grown on glia, we observed that neuronal processes tended to avoid the area around the electrodes, that the signal-to-noise ratio was lower than in neurons plated on a glial bed, and that propagation signals were not as notable in cultures lacking glia (data not shown).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A confluent glial bed could create a permissive environment for growth of axons closer to MEA electrodes than they might otherwise grow. Alternatively, glia could be an electrically resistive sheet that increases eAP amplitude across all electrodes by effectively decreasing the size of the electric field (Matsumura et al 2016). In neuronal cultures not grown on glia, we observed that neuronal processes tended to avoid the area around the electrodes, that the signal-to-noise ratio was lower than in neurons plated on a glial bed, and that propagation signals were not as notable in cultures lacking glia (data not shown).…”
Section: Discussionmentioning
confidence: 73%
“…This observation is consistent with physical elimination, or withdrawal, of the axonal process. In contrast, a decrease in spike-coupled transmembrane current in the axon at that electrode would not be expected to affect the size of the capacitive component of the eAP waveform at this site, although other explanations, such as withdrawal of glial processes leading to decreases in apparent signal size, cannot be ruled out (Matsumura et al 2016). Our data show that significant changes in axonal excitability can occur over several hours and imply that distinct portions of single axons can Decreases in the delays between the peak-scaled negative peak (arrowhead) and subsequent positive repolarization peaks (arrows) are consistent with a developmental decrease in spike width of the eAP at D6 between 11 and 26 DIV.…”
Section: Resultsmentioning
confidence: 92%
“…This could create a permissive environment for growth of axons closer to MEA electrodes than they might otherwise grow. Alternatively, glia could act as a resistive sheet that increases eAP amplitude across all electrodes (Matsumura et al, 2016). On bare arrays we observed that neuronal processes tend to avoid the area around the electrodes, that the signal-to-noise ratio was lower than in neurons plated on a glial bed and propagation signals were not as notable (data not shown).…”
Section: Signal Redundancymentioning
confidence: 71%
“…Recently, microsystems have created new opportunities for applying spatially and temporally controlled stimuli and recording cellular activity . Examples demonstrate the application of microchip devices for electrical stimulation and studies of signal propagation in cardiac myocyte networks .…”
Section: Introductionmentioning
confidence: 99%